The FACTORS RELATED TO THE PERCEPTION OF EARLY MARRIAGE AMONG STUDENTS AT SMA NEGERI 3 TOBOALI SOUTH BANGKA DISTRICT - Amelia Meda Septira; Dadang Herdiansyah; Munaya Fauziah; Nurfadhilah (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Early marriage can have many negative impacts, one of which is the health impact on the mother such as the risk of miscarriage and death, while the babies born are vulnerable to stunting and malnutrition. Finding the variables associated with students' perceptions of early marriage at SMA N 3 Toboali, South Bangka Regency, is the goal of this study. A cross-sectional study design is used in this investigation. The study was carried out between November 2023 and January 2024. Students of SMA Negeri 3 Toboali, South Bangka Regency, made up the research population. The research sample consisted of 83 respondents, and the sampling technique was complete sampling. A survey was used to collect the research data. The chi-square test was employed in bivariate data analysis51 (61.4%) of the respondents had unfavorable opinions. Forty respondents (48.2%) had a strong understanding of reproductive health. Of the respondents, 44 (53%) had parents who made more than $1 million. Peer pressure influenced the opinions of 46 individuals (55.4%) about early marriage. A total of 49 people (59%) chose mass media as a factor that supports the perception of early marriage. Based on statistical tests, it was found that the variables related to student perceptions at SMAN 3 Toboali, South Bangka Regency were knowledge of reproductive health (p=0.011) and mass media (p=0.007). Factors related to the perception of early marriage among students at SMAN 3 Toboali, South Bangka Regency are knowledge of reproductive health and mass media. In this case, education is needed from schools and health workers regarding the negative impacts of early marriage.